FINANCIAL DIMENSIONS SPECIFIC TO INSURANCE - VĂDUVA MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Insurance technology derives, on the one hand, from detailed legal provisions and therefore from the specifics of a certain contract, and, on the other hand, it derives from the existence of certain mechanisms, practices and operating procedures that embody economic efficiency, prudence, but also responsibility. A premium is the amount paid by an individual or company for an insurance policy. Premiums cover health, auto, home and life insurance. Once earned, the premiums are income for the insurance company, but also a liability because the insurance company must provide coverage for claims made against the policy. Non-payment of premiums by an individual or company leads to cancellation of the policy. Insurance compensation refers to the idea of returning the victim to the condition of the property before the damage and returning the property lost due to traffic accidents or cases insured by the victim, so that his property reaches what it would have been if the illegal act had not was committed.